Psychological stress among the displaced (Journal of the College of Basic Education, 2022)
The current research aims at studying the psychological pressure of the displaced, the researcher used in the current research gauge the psychological pressure of numbers researcher, applied research on a sample of displaced people in Pfdad province, the research found the following results: the high level of psychological stress among displaced people in general, and the results showed that The relative weight of psychological field of psychological pressure came first prize value of $ ) 42.993) and came second health field rank the value of ) 37.026) and was ranked third economic value of $ (34.306 ), and was ranked fourth area of security value of $ (24.793)), and came fifth social sphere prize value of $ 20.963) , regarding the identification of significance difference in the psychological pressure depending on the variable sex with displaced people, male and female, it has been shown that there is no difference between males and females in the scale Alnevsah.autam pressure to provide a set of recommendations for the views of the relevant